The extended law of star formation: the combined role of gas and stars - Dib, Sami; Hony, Sacha; Blanc, Guillermo A. (Monthly notices of the Royal Astronomical Society, 2017)
We present a model for the origin of the extended law of star formation in which the surface density of star formation ( SFR) depends not only on the local surface density of the gas ( g) but also on the stellar surface density ( ∗), the velocity dispersion of the stars and on the scaling laws of turbulence in the gas. We compare our model with the spiral, face-on galaxy NGC 628 and show that the dependence of the star formation rate on the entire set of physical quantities for both gas and stars can help explain both the observed general trends in the g − SFR and ∗ − SFR relations, but also, and equally important, the scatter in these relations at any value of g and ∗. Our results point out to the crucial role played by existing stars along with the gaseous component in setting the conditions for large scale gravitational instabilities and star formation in galactic discs.
Gesehen am 06.11.2018